An Enhanced Entity Model for Converting Relational to Non-Relational Documents in Hospital Management System Based on Cloud Computing. Issue 6 (2nd November 2022) - Samydurai, A.; Revathi, K.; Karthikeyan, L.; Vanathi, B.; Devi, K.
Abstract : In the past few years, several cloud services such as IBM cloud services, Microsoft service, Amazon web services as well as Google cloud platform services related databases are rising rapidly all over the world. In the case of a Relational database, it is easy to handle only a small amount of data. So to overcome the shortcomings, this paper proposes a Hospital Management System (HMS) using Mongo DB as a database. The Mongo DB is the classification of a document-related database that comes under the category of NoSQL database which is referred to as a non-relational database. Mongo DB aims in reducing the gap among two different types of scalable key-value databases such as fast and high scalable key-value databases. Also, this database reduces the time delay during the working of four operational modes such as selection, insertion, deletion, and updation. Furthermore, the Enhanced Entity-Relationship Model (EERM) for the HMS that is designed to manage the entire section of the hospital which includes the reception section, casualty section, details regarding the medical treatment, and employees. The HMS stores three million tuple entities and is loaded into the Mongo DB database. Also, the operation based on selection, insertion, deletion, and updation mode is evaluated. Therefore, the experimental analysis reveals that the proposed HMS using Mongo DB provides is highly efficient with less time delay, thus obtaining an effective system.